2016
DOI: 10.1080/14697688.2016.1176240
|View full text |Cite
|
Sign up to set email alerts
|

Smile and default: the role of stochastic volatility and interest rates in counterparty credit risk

Abstract: In this research, we investigate the impact of stochastic volatility and interest rates on counterparty credit risk (CCR) for FX derivatives. To achieve this we analyse two real-life cases in which the market conditions are different, namely during the 2008 credit crisis where risks are high and a period after the crisis in 2014, where volatility levels are low. The Heston model is extended by adding two Hull-White components which are calibrated to fit the EURUSD volatility surfaces. We then present future ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In the case of expected exposure, it appears that the two-dimensional decomposed approximation is already close to the full-scale Monte Carlo solution. This is in line with Simaitis et al (2016), where it is found that for expected exposure, a time dependent volatility function can be used, whereas only for non-linear exposures (such as expected positive or negative exposure), a full stochastic volatility model should be used.…”
Section: Stochastic Volatilitysupporting
confidence: 70%
“…In the case of expected exposure, it appears that the two-dimensional decomposed approximation is already close to the full-scale Monte Carlo solution. This is in line with Simaitis et al (2016), where it is found that for expected exposure, a time dependent volatility function can be used, whereas only for non-linear exposures (such as expected positive or negative exposure), a full stochastic volatility model should be used.…”
Section: Stochastic Volatilitysupporting
confidence: 70%
“…In recent years, there has been an increasing interest in modelling credit risk by practitioners as well as academics (see e.g., Gregory, 2015, Green, Kenyon, & Dennis, 2014, Sourabh, Hofer, & Kandhai, 2018, De Graaf, Feng, Kandhai, & Oosterlee, 2014, de Graaf, Kandhai, & Reisinger, 2018, Simaitis, de Graaf, Hari, & Kandhai, 2016, Anagnostou & Kandhai, 2019. Portfolio credit risk models are concerned with the occurrence of large losses due to defaults or deteriorations in credit quality.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, stochastic interest rate is crucial for option pricing because it ensures proper discounting of future payoffs. In recent literatures [14][15][16][17], Hull-White stochastic interest rate which is analytically tractable has been incorporated into one-factor stochastic volatility model for pricing path-dependent options. Therefore, the model which incorporates multifactor stochastic volatility and stochastic interest rate may be more reasonable for pricing barrier options.…”
Section: Introductionmentioning
confidence: 99%